G312 Improving appropriate and safe management of children in primary care through direct access to specialist paediatric expertise. (27th April 2016) - Cheung, R; Lemer, C
Abstract : Aims: We report on the Evelina London Children's Hospital (ELCH)'s one year experience of introducing the Children's Assessment and Referral Service (CARS), an integrated programme to improve primary care doctors' access to secondary care expertise. Through improved access to "just-in-time" advice on management and referral urgency for local general practitioners, we aim to improve primary care diagnosis and management of complex paediatric problems; facilitate specialist paediatric reviews by the right person, at the right time; and to reduce unnecessary referrals to emergency department. Methods: In October 2014, we introduced CARS, providing advice and triage to support GPs with the management of paediatric patients, comprising 3 key elements: Telephone advice 11am–7pm: A general paediatric consultant available to GPs. Email advice within 24 h Monday–Friday Rapid access outpatient review: A rapid access outpatient facility for children who would benefit from a prompt assessment, but who do not have urgent clinical need which indicates they should attend A&E. Results: Utilisation has increased month on month from onset. Most recent data shows 12.6 calls and 10.7 emails per week. For 34% of phone calls in past 3 months, GPs reported that the purpose of their call was for advice on management in primary care. Of these, 4.7% (9 patients) were deemed to require an outpatient review, uncovering an under-recognition of problem requiring specialist review. 46% of calls were reported to be seeking advice for outpatient referral need/urgency. Of these, 22% received advice which obviated the need for outpatient referral. For 5 patients, a request for outpatient referral resulted in advice that the child required emergency same-day review, which ensured acutely unwell children were recognised appropriately and received timely review and treatment. Primary care colleagues have provided overwhelmingly positive feedback on the service. Conclusion: We have instigated a coordinated program of improving the remote provision of paediatric expertise to primary care, which has resulted in improving the appropriateness of hospital utilisation, both in reducing unnecessary outpatient referrals but more importantly recognising and mitigating the risk of under-recognition of paediatric problems in primary care requiring urgent specialist intervention.